Ability of a New Fear of Falling Scale in Assessing Fall Risk and Its Correlation with Functional Balance in Community-Dwelling Older Adults - Puttipong Poncumhak; Arunrat Srithawong; Wilairat Namwong; Winut Duangsanjun (Physical Activity and Health)
Purpose: The Fear of Falling 10-Rating Scale (FOF-10) was developed to assess fear of falling and fall risk among community-dwelling older adults. This study aims to evaluate the utility of the FOF-10 in assessing fear of falling and predicting fall events by comparing its performance with established standard assessments for fall risk. Methods: This cross-sectional study included 107 older adults aged 60 years and above, comprising both males and females. Participants underwent assessments of baseline characteristics and a retrospective evaluation of fall history over the past six months. Subsequently, they were assessed using the FOF-10, the Falls Efficacy Scale-International (FES-I), and the Timed Up and Go (TUG) test. Results: The participants had a mean age of 74 years, with 45.79% reporting at least one fall in the preceding six months. Significant differences were observed in the FOF-10, TUG, and FES-I scores between fallers and non-fallers (p < 0.001). The FOF-10 showed significant associations with TUG, FES-I, and the number of falls (rho = 0.929, 0.830, and 0.573, respectively; p < 0.001 for all). Comparative analysis of discriminatory ability revealed that the FOF-10 demonstrated the highest performance in distinguishing fallers from non-fallers, followed by FES-I and TUG. Conclusions: This study demonstrates that the FOF-10 is a practical tool for assessing fear of falling and fall events among older adults. The scale is simple, requires no complex equipment, and is time-efficient. Participants who self-reported a score of 4 or higher on the FOF-10 were indicative of a higher likelihood of experiencing falls.